Botulinum Toxin Injections as an Adjunct to Surgical Lip Repositioning for Gummy Smile Treatment - Queiroz, Thallita Pereira (2022)
Background: An attractive smile depends on the proper proportion and arrangement of lip, teeth gingiva scaffold. The ideal smile is the exposure of the entire length of maxillary teeth with 1 mm gingiva. A gingival display exceeding 3 mm is unpleasant and termed gummy smile (GS). Lip repositioning is a simple surgical procedure intended to minimize the gingival display by removing a strip of mucosa and shortening the vestibular depth. Botulinum toxin injecting overactive muscles with measured quantities results in a reduction of muscle activity, relaxing the lip muscles and decreasing upward pull on the lip. There are some contraindications: patients with short lips and gingival exposures less than 3 mm. Purpose: This case report describes the successful management of GS of a young man. Case Report: The procedures were performed and these techniques resulted in shortened vestibule and restricted the muscle pull of the elevator muscles of the lip, reducing gingival display when the patient smiles. Surgical lip repositioning can be a minimally invasive alternative to orthognathic surgery. Botulinum Toxin injections can be a useful adjunct to enhance the esthetics and improve patient satisfaction, being a more conservative and immediate nonsurgical treatment modality available. Conclusions: In this way, the clinical case report demonstrated that lip repositioning surgery combined to botulinum toxin injections promising outcomes in the GS correction. The effect showed a marked reduction in gingival display at the 4-years follow-up.